2021
DOI: 10.1038/s41598-020-80603-8
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular safety and efficacy of metformin-SGLT2i versus metformin-sulfonylureas in type 2 diabetes: systematic review and meta-analysis of randomized controlled trials

Abstract: Diabetes is a serious threat to global health and among the top 10 causes of death, with nearly half a billion people living with it worldwide. Treating patients with diabetes tend to become more challenging due to the progressive nature of the disease. The role and benefits of combination therapies for the management of type 2 diabetes are well-documented, while the comparative safety and efficacy among the different combination options have not been elucidated. We aimed to systematically synthesize the evide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Our data strongly suggest that MET should be a frontline drug for the treatment of diabetic patients with HFrEF. Combination therapy with MET and SGLT2i has been shown safe and efficacious in patients with DM 50 . Combined therapy of these patients with MET and SGLT2 inhibitors warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…Our data strongly suggest that MET should be a frontline drug for the treatment of diabetic patients with HFrEF. Combination therapy with MET and SGLT2i has been shown safe and efficacious in patients with DM 50 . Combined therapy of these patients with MET and SGLT2 inhibitors warrants further research.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent systematic review concluded that metformin significantly lowered all-cause mortality and cardiovascular events in patients with T2DM and mild/moderate chronic kidney disease ( 163 ). Similarly, a meta-analysis with the objective of determining the cardiovascular benefits of metformin in combination with newer anti-diabetic drugs including incretins (GLP-1 agonists), dipeptidyl peptidase-4 (DPP-4) inhibitors, and sodium-glucose co-transporter 2 (SGLT2) inhibitors revealed both positive and neutral effects of adding metformin ( 164 , 165 ). Nonetheless, in the absence of appropriately designed placebo-driven randomized control studies (RCTs) that include comparison with GLP-1 agonists, DPP-4 and SGLT2 inhibitors, doubt persists if, in fact, metformin does reduce the cardiovascular risk associated with diabetes ( 166 ).…”
Section: Metformin and Mortality In Diabetic Patientsmentioning
confidence: 99%
“…safe and e cacious in patients with DM 52 . Combined therapy of these patients with MET and SGLT2 inhibitors warrants further research.…”
Section: Discussionmentioning
confidence: 97%